Perception and Cognition in Translating Chinese Landscape Poetry : A Case Study of Liu Zongyuan’s poem River Snow - Zhu, Chunshen (TTR)

(untitled) (Association canadienne de traductologie, 1999)
AbstractPerception and Cognition in Translating Chinese Landscape Poetry : A Case Study of Liu Zongyuan's Poem River Snow — The article, based on the Heideggerian dichotomy of calculative versus meditative thinking and with reference to Arnheim's psychology of visual art, argues that a poem thinks in the way it makes the reader think, and it is the poetic (meditative) way of thinking that a poem inspires that determines the poem's being a poem. Through an intensive case study of a classical Chinese poem, it tries to illustrate how a poem's textual formulation can set a reader thinking. It follows that to translate a poem as a poem, the translator must approach the source text with the mind open and released to the meditative thinking it inspires as gift — by stepping back from calculative thinking which strives to represent objects in their material accuracy, so as to produce a target text that will set the target reader thinking in a similar, meditative way.